The Influence of Motivation and Discipline on Nurse Performance at Dr. H. Chasan Boesoirie Regional Hospital - Irwan Ali; Abd. Hakim Husen (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
Nurse performance is a crucial factor in improving the quality of hospital services. This study aims to analyze the influence of motivation and work discipline on nurse performance at Dr. H. Chasan Boesoirie Regional Hospital. A quantitative survey method was applied with 149 respondents, and data were analyzed using Path Analysis. The results show that motivation (t = 9.528; p = 0.000) and work discipline (t = 4.040; p = 0.000) significantly and positively affect nurse performance. These findings indicate that enhancing motivation and discipline contributes directly to increasing productivity and service quality.